Is groundwater fauna impacted by swine effluent fertigation? - Centurião, Thaynara Davalo; Silva, William Marcos da; Gabas, Sandra Garcia (Ciência e Natura, 2022)
In this study, we tested whether the fertigation of swine effluent impacts the underground aquatic fauna of porous free aquifer. The physicochemical parameters of groundwater were determined and correlated with the fauna present in the aquifer on fertigated and non-fertigated areas with swine effluents treated in biodigester. Seasonality influences on water quality were also tested. For this purpose, groundwater samples from pre-existing farmer-owned water wells and piezometers using the bailer and 65-Micra mesh net for filtering organisms. The physicochemical results show that there may be some changes in quality parameters. We recorded twelve invertebrate taxa, with Acari and Copepoda being the most prevalent. Colonization of aquatic species may have been limited by the emergence of exotic organisms and water quality.